Iowa Birdline update, August 1, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for August 1, 1988. Highlights of the update include sightings of three Heron species, three Tern species, American Avocets, and Ruddy Turnstones. Also of note was the continued presence of a pair of Northern Mockingbirds that were first spotted in mid-June. Epson - sheet feed/flatbed